ANALISA PENERAPAN SENSOR SUHU MENGGUNAKAN ARDUINO UNO DI DALAM SISTEM PERTANIAN GREENHOUSE: SENSOR DHT22 - Yehezkiel Kharisma Yonatan; Ayub Trisna Mukti, Rafli Nur Firmansyah, Paduloh (ADISAM PUBLISHER, 2026)
Modern agriculture increasingly relies on technology to optimize efficiency and productivity. Temperature management plays a critical role in plant growth and yield, making it a key focus in agricultural innovation. This research explores the application of a DHT22 temperature and humidity sensor integrated with an Arduino Uno microcontroller to develop a temperature monitoring system in agricultural environments, specifically in greenhouses. The system collects real-time environmental data, such as temperature and humidity, and enables remote monitoring through a monitor inside a computer. By analyzing the collected data, farmers can implement automated responses, such as activating cooling or irrigation systems, to maintain optimal growing conditions. The research methodology involved hardware design, programming, data collection, analysis, and evaluation of the system. The results demonstrate the effectiveness of the system in improving environmental monitoring and decision-making for resource optimization. This study highlights the potential into sustainable and efficient agricultural practices.